HUBUNGAN PERNIKAHAN DINI, EKONOMI KELUARGA,MEDIA SOSIAL DENGAN KEJADIAN PERCERAIAN PADA WANITA PUS DI KECAMATAN BANDUNGAN KABUPATEN SEMARANG TAHUN 2017 - Novita Haloho; Dharminto Dharminto; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2018)
Divorce is the end of a marital relationship for a reason based on a judge’s decision. Divorce in Bandungan sub-district is 8% of 577 divorce cases in Semarang. The purpose of this study is to analyze the relationship of early marriage, family economy, social media with the incidence of divorce. The type of this research is an explanatory research with design cross sectional study. The population of this study is 8.852 women in Bandungan District and The sample  is 95 women were selected by simple random sampling. Data were collected by using questioner and analyzed with univariat, descriptive bivariat and analytic bivariat with chi-square test, continuity correction method. The result of univariat got early marriage (56,8%) , high family economics (69,5%) and use social media (58,9%). The result of descriptive bivariat showed that divorce more occured in women married <21 years (25,9%), had a family economy >UMR (21,1%), did not use social media (32,2%). From the 3 variables, none were significantly associated with the incidence of divorce, early marriage (0,084), family economy (0,572), social media (p-value=0,098). Suggestions that can be given is delay of marriage age and marriage counseling held by KUA.